Analisis Motivasi Nelayan Tangkap dalam Strategi Diversifikasi Pendapatan Rumah Tangga di Kelurahan Pasar Bawah Kabupaten Bengkulu Selatan - Ikwan Sahputra; Herri Fariadi; Evi Andriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Most capture fishers in Pasar Bawah Village, Pasar Manna Sub-district, South Bengkulu Regency have adopted income source diversification as a household economic strategy. This approach is undertaken because fishing activities are highly dependent on weather conditions and fishing seasons, which are often unpredictable. During periods of high waves, many fishers are unable to go to sea for several days or even weeks, prompting them to seek alternative livelihoods to meet their daily household needs. This study aims to examine the level of motivation among capture fishers to diversify household income sources and to analyze the factors associated with such motivation in Pasar Bawah Village, Pasar Manna Sub-district, South Bengkulu Regency. The research employed a quantitative descriptive method using descriptive analysis and the Spearman Rank correlation (Rs) test. The results indicate that the motivation of capture fishers to diversify household income sources is categorized as high, with an average score of 96.71. All variables examined show positive and significant relationships with fishers’ motivation to diversify income sources. Income uncertainty from fishing activities (X₁) exhibits the highest correlation coefficient at 0.684, indicating a very strong relationship, followed by extreme weather conditions and high-wave seasons (X₂) with a correlation value of 0.413, reflecting a strong relationship. Furthermore, encouragement from family members (X₃) shows a correlation coefficient of 0.306, indicating a moderately strong relationship, while proximity to markets and urban centers (X₄) has a correlation value of 0.289, also indicating a moderately strong relationship. The intensity of extension services (X₅) records a correlation coefficient of 0.256, suggesting a moderately strong relationship.